Implementasi Gerakan Jamaah Masjid dalam Menumbuhkan Pendidikan Sosial di Masyarakat: Studi Masjid K.H. Sudja’ Gamping Yogyakarta - Salman Fajar Abdul Rokhman; Fajar Rachmadhani (CV. Lentera Literasi Indonesia, 2026)
Mosques have a crucial historical role in Islam, not only as places of worship but also as centers of education, social work, and community empowerment. However, these functions are often narrowed in meaning, limited to mere ritual activities. This study aims to deeply explore how the mosque community movement can play a role in fostering social education in the community, using the K.H. Sudja' Mosque in Gamping, Yogyakarta as a case study. This mosque is known for its active involvement in managing religious and social activities within the urban community. This study employed descriptive qualitative approach using data collection techniques including in-depth interviews, participant observation, and program documentation. The analysis was conducted through data reduction, data presentation, and conclusion drawing, as well as triangulation to maintain the validity of the findings. The research results show that the implementation of the community movement encompasses religious programs (religious study groups, thematic studies, TPA), social programs (basic food assistance, charity, health services), and empowerment (skill trainings, economic development). This program has successfully increased collective awareness, community participation, and the practice of Islamic values in daily life. The challenges encountered include limited funding, minimal participation from the younger generation, and a lack of cadre development. However, the mosque can collaborate with various community elements, including religious leaders, mosque youth, and social institutions. This research approves that the community movement has great potential as a model for community-based social education and religious values, which is significant to be continuously strengthened and developed.